Predictors Predictors Of Self-Dissatication And Self-Actualization On Learning Success Of Early Adolescent Students - Fakhri (Jurnal Pengembangan Profesi Guru dan Dosen, 2025)
: Students in the early adolescent phase tend to experience personal instability, identity search, the emergence of fear, and many other adolescent problems that arise in this phase. Such conditions will be very difficult for all students to face. Students are still lacking in self-actualization and students also become dissatisfied with themselves, causing a decline in academic achievement. The phenomenon that occurs in students who have no self-actualization causes a decline in learning and in everyday life. The purpose of this study is to describe the relationship between self-dissatisfaction and self-actualization to student academic achievement at MTsS Darul Ulum. This study uses a quantitative method with a correlation approach. The research sample amounted to 89 students. Data were collected through questionnaires that measured aspects of self-dissatisfaction and self-actualization. Data analysis was carried out using multiple linear regression techniques to test hypotheses regarding the relationship between these variables. After the data was obtained, the data was analyzed using SPSS version 20. Based on the results of the analysis of the research data, the results showed that both variables have a significant relationship to academic achievement. The correlation index of the self-dissatisfaction variable to academic achievement is 0.063. Furthermore, the regression coefficient between self-actualization and student learning achievement was 0.048. This study reports that self-dissatisfaction and self-actualization play a significant role in the learning achievement of adolescent students.